Aligning Hearing Aid and Cochlear Implant Improves Hearing Outcome in Bimodal Cochlear Implant Users. Issue 10 (December 2020) - Holtmann, Laura Christine; Janosi, Anna; Bagus, Heike; Scholz, Tim; Lang, Stephan; Arweiler-Harbeck, Diana; Hans, Stefan
Abstract : Objective: Patients with unilateral deafness and residual hearing on the contralateral ear can benefit from a cochlear implant (CI) on one side and a hearing aid (HA) on the other. However, hearing improvement among these patients is heterogenous. Interindividual differences in bimodal benefit may be caused by a mismatch of CI and HA. The aim of this study was to clinically apply a HA fitting strategy and to evaluate hearing outcome with and without a dedicated bimodal fitting formula. Study Design: Prospective non-randomized study. Setting: Tertiary referral center. Patients: Twelve patients using a CI processor and a conventional HA were enrolled. Before and after the new HA had been adjusted to the patient and linked to the CI, pure-tone audiometry and localization tests were performed. Speech perception was determined in quiet and noise. Tests were repeated after 6 and 12 weeks. To evaluate the subjective listening comfort two questionnaires (Oldenburg Inventory and HISQUI19 ) were assessed. Intervention: Therapeutic. Results Main outcome measure: Word recognition in quiet, sentence recognition in noise. Speech perception in noise improved significantly: directed suppression of noise helped to segregate the target speech signal from a mixture of sounds or competing speakers. Evaluation of the questionnaires revealed a positive subjective hearing experience compared with patients' initial settings of the devices. Conclusion: By linking CI and HA hearing and speech perception can be improved. However, good counselling at the outset is essential to obtain enhanced outcome.